Experimental investigation on biodiesel?diesel blends in a single-cylinder DI diesel engine - Venu H.; Appavu P. (Taylor and Francis Ltd., 2025)
The present study analyses the utilisation of biodiesel?diesel blends in a single-cylinder diesel engine. Biodiesel is prepared via conventional transesterification with standard conditions (60C reaction temperature, 1% by wt. catalyst, 7.5:1 molar ratio and 120 min reaction time). The test engine utilised is a single-cylinder naturally aspirated direct injection diesel engine. The test engine is operated at 100% load with different engine speeds ranging from 1000 to 2400 rpm. Performance, combustion and emission characteristics were analysed at different engine speeds. The MB10 blend (10% biodiesel + 90% diesel) has resulted in higher brake power of 7.43%, lowered brake-specific fuel consumption and carbon dioxide by 7.49% and 7.6%, respectively. Also, it can be concluded that the MB10 blend lowered the smoke by 24% and hydrocarbon by 10.34% with respect to neat diesel. The MB20 blend resulted in a lowered CO profile than the CO profile of diesel fuel by about 0.84%. However, the MB10 blend?s average CO profile is improved by 1.97% than mineral diesel. These results are compromised with higher CO and NOx profiles of 2.4% and 8.9%, respectively. ? 2024 Informa UK Limited, trading as Taylor & Francis Group.